On Domains that Admit Well-Behaved Strategy-Proof Social Choice Functions - CHATTERJI, Shurojit (Institutional Knowledge at Singapore Management University, 2013)
In this paper, we investigate domains that admit “well-behaved” strategy-proof social choice functions. We show that if the number of voters is even, then every domain that satisfies a richness condition and admits an anonymous, tops-only, unanimous and strategy-proof social choice function, must be semi-single-peaked. Conversely every semi-single-peaked domain admits an anonymous, tops-only, unanimous and strategy-proof social choice function. Semi-single-peaked domains are generalizations of single-peaked domains on a tree introduced by Demange (1982).